Penyelesaian Sengketa Tapal Batas Antara Desa Jasri dengan Desa Perasi Melalui Upaya Mediasi - I Kadek Dwipyana; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2022)
There are still many border disputes that occur in Bali, especially in Karangasem Regency, which involves two neighboring villages, namely the Jasri Traditional Village and the Perasi Traditional Village. This is based on legal uncertainty related to existing boundaries and also because of social factors between community relations that cause conflict problems. The purposes of this study are to reveal the factors that cause boundary disputes between Jasri Traditional Villages and Perasi Traditional Villages and to resolve border disputes between Jasri Traditional Villages and Perasi Traditional Villages. This research is an empirical legal research with a sociological approach. Data collection techniques were carried out by interview and literature study. Sources of legal materials used are primary and secondary legal sources. In analyzing the data, the researcher used flow model analysis techniques. The results of the study reveal that with the existence of Law Number 30 of 1999 concerning Arbitration, Permendagri Number 45 of 2016 concerning Guidelines for Establishing and Affirming Village Boundaries and Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts, both parties need to know so that their rights rights and obligations are not violated according to existing regulations.